Optical multilayers
Patent Information
- Application Number
- JP2021006233
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-01-19
- Publication Date
- 2025-01-09
- Estimated Expiration
- 2041-01-19
AI Technical Summary
【0010】 本発明によれば、保護フィルムが設けられていない表面を有する偏光子を備える光学積層体であって、偏光子の耐久性の低下が抑制され、偏光子と他の部材間での密着性が高い、光学積層体を提供することができる。
Smart Images

Figure 0007610988000007 
Figure 0007610988000001 
Figure 0007610988000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an optical laminate, and also to an image display device having the optical laminate. [Background technology]
[0002] 2. Description of the Related Art Conventionally, in image display devices, a method has been adopted in which an optical laminate having anti-reflection properties is disposed on the viewing side of an image display panel to suppress a decrease in visibility due to reflection of extraneous light.
[0003] Circularly polarizing plates constituted by a polarizer and a retardation film are known as optical laminates having antireflection properties.
[0004] In a circular polarizing plate, external light heading toward an image display panel is converted into linearly polarized light by a polarizer, and then converted into circularly polarized light by a subsequent retardation layer. The external light converted into circularly polarized light is reflected by the surface of the image display panel, but the direction of rotation of the polarization plane is reversed during this reflection, and the light is converted into linearly polarized light by a retardation layer, and then blocked by the subsequent polarizer. As a result, the light is significantly prevented from being emitted to the outside.
[0005] When an image display device is used in a harsh environment, there is a problem that the optical properties of the polarizer tend to deteriorate. JP2013-105036A describes that a polarizer having excellent durability can be obtained by increasing the content of boric acid in the polarizer. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2013-105036 A Summary of the Invention [Problem to be solved by the invention]
[0007] In the optical laminate, the durability of the polarizer can be improved by laminating protective films on both sides of the polarizer. Although a configuration in which a protective film is provided on only one surface of the polarizer is advantageous from the viewpoint of thinning, it has a problem of lower durability compared to a configuration in which protective films are laminated on both sides of the polarizer. In addition, the present inventors have found that a configuration in which a protective film is provided on only one surface of the polarizer has a problem of low adhesion between the polarizer and other members, such as a retardation film, laminated on the surface of the polarizer that does not have the protective film.
[0008] The present invention aims to provide an optical laminate including a polarizer having a surface on which no protective film is provided, in which a decrease in the durability of the polarizer is suppressed and adhesion between the polarizer and other components is high. [Means for solving the problem]
[0009] The present invention provides an optical laminate, an image display device, and a method for producing an optical laminate, which are described below. [1] An optical laminate comprising a polarizer containing a polyvinyl alcohol-based resin and a retardation film containing a cured product of a polymerizable liquid crystal compound, An optical laminate having, between the polarizer and the retardation film, a first adhesive layer provided in contact with the polarizer, and a second adhesive layer provided in contact with the retardation film. [2] The first adhesive layer has a tensile modulus of elasticity of 2000 MPa or more at a temperature of 25°C; The optical laminate according to [1], wherein the second adhesive layer has a tensile modulus of elasticity of 1900 MPa or less at a temperature of 25°C. [3] The first adhesive layer is a cured layer of a cationic polymerizable adhesive, The optical laminate according to [1] or [2], wherein the second adhesive layer is a cured layer of a radically polymerizable adhesive. [4] The optical laminate according to any one of [1] to [3], wherein the retardation film includes a λ / 4 layer. [5] The optical laminate according to any one of [1] to [4], which is an anti-reflection polarizing plate. [6] An image display device comprising an image display panel and the optical laminate according to [5] arranged on a front surface of the image display panel. [7] The image display device according to [5], wherein the image display panel is an organic electroluminescence (EL) display panel. [8] A method for producing the optical laminate according to any one of [1] to [5], applying a first adhesive to a surface of the polarizer and curing the first adhesive to form a first adhesive layer; laminating the first adhesive layer formed on the surface of the polarizer and the retardation film with a second adhesive therebetween, and curing the second adhesive to form a second adhesive layer. Effect of the Invention
[0010] According to the present invention, it is possible to provide an optical laminate including a polarizer having a surface on which no protective film is provided, in which a decrease in the durability of the polarizer is suppressed and adhesion between the polarizer and other components is high. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of an optical laminate of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, an embodiment of the present invention will be described with reference to the drawings, but the present invention is not limited to the following embodiment. In all of the drawings, the scale of each component is appropriately adjusted to make it easier to understand, and the scale of each component shown in the drawings does not necessarily match the scale of the actual component.
[0013] <Optical laminate> The optical laminate according to the present invention includes a polarizer containing a polyvinyl alcohol resin and a retarder containing a cured product of a liquid crystal compound, and includes a first adhesive layer provided between the polarizer and the retarder in contact with the polarizer and a second adhesive layer provided in contact with the retarder. In the optical laminate according to the present invention, the presence of the first adhesive layer and the second adhesive layer suppresses a decrease in the durability of the polarizer, and an optical laminate having high adhesion between the polarizer and other members can be provided.
[0014] An embodiment of an optical laminate according to the present invention will be described with reference to Fig. 1. The optical laminate 100 shown in Fig. 1 has a linear polarizer 130, a first adhesive layer 150, a second adhesive layer 160, and a retarder 140, in this order.
[0015] The linear polarizer 130 includes a protective layer 131 and a polarizer 132, in this order, from the front side. The retarder 140 includes a first retardation layer and a second retardation layer 142, in this order, from the linear polarizer 130 side. The first retardation layer 141 and the second retardation layer 142 may be bonded to each other by an interlayer bonding layer 143.
[0016] The optical laminate may have, for example, a square shape in plan view, preferably a square shape having long and short sides, more preferably a rectangle. Each layer constituting the optical laminate may have rounded corners, cut-out ends, or holes.
[0017] The optical laminate can be used, for example, in an image display device, etc. The image display device is not particularly limited, and examples thereof include an organic electroluminescence (organic EL) display device, an inorganic electroluminescence (inorganic EL) display device, a liquid crystal display device, and an electroluminescence display device.
[0018] [Linear polarizing plate] The linear polarizing plate 130 can be formed by laminating a protective layer 131 on one side of a polarizer 132. When unpolarized light is incident on the linear polarizing plate 130, the linear polarizing plate 130 has the property of transmitting linearly polarized light having a vibration plane perpendicular to the absorption axis. The linear polarizing plate 130 contains a polyvinyl alcohol (hereinafter sometimes abbreviated as "PVA")-based resin as the polarizer 132.
[0019] The thickness of the linear polarizer 130 is, for example, not less than 2 μm and not more than 100 μm, and preferably not less than 5 μm and not more than 60 μm.
[0020] [Polarizer] A polarizer obtained by dyeing a polyvinyl alcohol-based resin film with iodine and uniaxially stretching the film can be used.
[0021] Polyvinyl alcohol resins can be produced by saponifying polyvinyl acetate resins. Polyvinyl acetate resins can be copolymers of vinyl acetate and other monomers copolymerizable with vinyl acetate, in addition to polyvinyl acetate, which is a homopolymer of vinyl acetate. Examples of other monomers copolymerizable with vinyl acetate include unsaturated carboxylic acids, olefins, vinyl ethers, unsaturated sulfonic acids, and acrylamides having an ammonium group.
[0022] The degree of saponification of the polyvinyl alcohol resin is usually about 85 to 100 mol%, preferably 98 mol% or more. The polyvinyl alcohol resin may be modified, and for example, polyvinyl formal or polyvinyl acetal modified with aldehydes can be used. The average degree of polymerization of the polyvinyl alcohol resin is usually about 1,000 to 10,000, preferably about 1,500 to 5,000. The average degree of polymerization of the polyvinyl alcohol resin can be determined in accordance with JIS K 6726 (1994). If the average degree of polymerization is less than 1,000, it is difficult to obtain a preferable polarizing performance, and if it exceeds 10,000, the film processability may be poor.
[0023] Other methods for producing a linear polarizing plate containing a polyvinyl alcohol-based resin film include a method including a step of first preparing a substrate film, applying a solution of a resin such as a polyvinyl alcohol-based resin onto the substrate film, and performing drying to remove the solvent to form a resin layer on the substrate film. A primer layer can be formed in advance on the surface of the substrate film on which the resin layer is to be formed. As the substrate film, a resin film such as PET or a film using a resin that can be used for a protective layer described later can be used. As the material for the primer layer, a resin obtained by crosslinking a hydrophilic resin used for a linear polarizing plate can be used.
[0024] Next, the amount of solvent such as water in the resin layer is adjusted as necessary, and then the base film and the resin layer are uniaxially stretched, and then the resin layer is dyed with a dichroic dye such as iodine to adsorb and align the dichroic dye in the resin layer. Next, if necessary, the resin layer with the dichroic dye adsorbed and align is treated with an aqueous boric acid solution, and a washing step is performed to wash off the aqueous boric acid solution. This produces a resin layer with the dichroic dye adsorbed and align, i.e., a polarizer. A known method can be used for each step.
[0025] The uniaxial stretching of the substrate film and the resin layer may be performed before dyeing, during dyeing, or during boric acid treatment after dyeing, and uniaxial stretching may be performed at each of these multiple stages. The substrate film and the resin layer may be uniaxially stretched in the MD direction (film conveying direction), in which case they may be uniaxially stretched between rolls with different peripheral speeds, or may be uniaxially stretched using a heated roll. The substrate film and the resin layer may be uniaxially stretched in the TD direction (direction perpendicular to the film conveying direction), in which case a so-called tenter method can be used. The substrate film and the resin layer may be stretched by dry stretching in the air, or by wet stretching in a state in which the resin layer is swollen with a solvent. In order to exhibit the performance of the polarizer layer, the stretching ratio is 4 times or more, preferably 5 times or more, and particularly preferably 5.5 times or more. There is no particular upper limit to the stretching ratio, but it is preferably 8 times or less from the viewpoint of suppressing breakage and the like.
[0026] The polarizer produced by the above method may be used as a linear polarizing plate by peeling off the substrate film or together with the substrate film. According to the above method, the substrate film can be peeled off, so that the linear polarizing plate can be made even thinner.
[0027] The thickness of the polarizer including the polyvinyl alcohol-based resin film is, for example, 2 μm or more and 40 μm or less. The thickness of the polarizer may be 5 μm or more, 20 μm or less, 15 μm or less, or even 10 μm or less.
[0028] [Protective layer] The protective layer 131 has a function of protecting the surface of the polarizer 132. In the optical laminate, the linear polarizer 130 is disposed so that the protective layer 131 is on the front side of the polarizer 132. The linear polarizer 130 may not have the protective layer 131.
[0029] The protective layer 131 can be an organic layer or an inorganic layer. The protective layer 131 may be a base film used in the manufacturing process of the polarizer layer 132. The organic layer can be formed using a composition for forming a protective layer, such as a (meth)acrylic resin composition, an epoxy resin composition, a polyimide resin composition, or the like. The composition for forming a protective layer may be of an active energy ray curable type or a thermosetting type. The inorganic layer can be formed from, for example, silicon oxide or the like. When the protective layer 131 is an organic layer, the protective layer may be what is called a hard coat layer.
[0030] When the protective layer 131 is an organic layer, for example, an active energy ray curable composition for forming a protective layer can be applied to a substrate film, and the active energy can be irradiated to cure the composition, thereby producing a protective layer. The above description of the substrate film is applied to the substrate film. The substrate film is usually removed by peeling. Examples of methods for applying the composition for forming a protective layer include a spin coating method. When the protective layer 131 is an inorganic layer, the protective layer can be formed by a sputtering method, a vapor deposition method, or the like. When the protective layer 131 is an organic layer or an inorganic layer, the thickness of the protective layer 131 may be, for example, 0.1 μm or more and 10 μm or less, and preferably 0.5 μm or more and 5 μm or less.
[0031] As the protective layer 131, for example, a resin film having excellent transparency, mechanical strength, thermal stability, moisture blocking properties, isotropy, stretchability, etc. may be used. The resin film may be a thermoplastic resin film. Specific examples of such resins include cellulose resins such as triacetyl cellulose; polyester resins such as polyethylene terephthalate and polyethylene naphthalate; polyethersulfone resins; polysulfone resins; polycarbonate resins; polyamide resins such as nylon and aromatic polyamide; polyimide resins; polyolefin resins such as polyethylene, polypropylene, and ethylene-propylene copolymers; cyclic polyolefin resins having cyclo- and norbornene structures (also called norbornene-based resins); (meth)acrylic resins; polyarylate resins; polystyrene resins; polyvinyl alcohol resins, and mixtures thereof. When protective layers are laminated on both sides of the polarizer layer, the two protective layers may be of the same type or different types. The thickness of the resin film may be, for example, 3 μm or more and 50 μm or less, and preferably 5 μm or more and 30 μm or less.
[0032] [First adhesive layer, second adhesive layer] The first adhesive layer 150 is provided in contact with the surface of the polarizer 132 opposite to the protective layer 131 side. The first adhesive layer 150 can be formed by curing the first adhesive. The first adhesive layer 150 has a tensile modulus of elasticity of preferably 2000 MPa or more at a temperature of 25° C., more preferably 2100 MPa or more, and even more preferably 2200 MPa or more. The first adhesive layer 150 has a tensile modulus of elasticity of, for example, 4000 MPa or less at a temperature of 25° C. When the tensile modulus of elasticity of the first adhesive layer 150 is within the above-mentioned range, it is possible to suppress the outflow of the dichroic dye such as iodine adsorbed and oriented in the polarizer 132 from the polarizer 132, thereby improving the durability of the polarizer 132 and improving the durability of the optical properties of the optical laminate.
[0033] The second adhesive layer 160 is provided in contact with the surface of the retarder 140 facing the linear polarizer 130. The second adhesive layer 160 can be formed by curing the second adhesive. The second adhesive layer 160 has a tensile modulus of elasticity of preferably 1900 MPa or less at a temperature of 25° C., more preferably 1800 MPa or less, and even more preferably 1700 MPa or less at a temperature of 25° C. The second adhesive layer 160 has a tensile modulus of elasticity of, for example, 100 MPa or more at a temperature of 25° C. When the tensile modulus of elasticity of the second adhesive layer 160 is within the above-mentioned range, the adhesion between the polarizer 132 and the retarder 140 in the optical laminate 100 can be improved. When the surface of the retarder 140 facing the polarizer 132 contains a cured product of a polymerizable liquid crystal compound, there is a significant problem of low adhesion between the polarizer 132 and the retarder 140. However, according to the present invention, even when the surface of the retarder 140 facing the polarizer 132 contains a cured product of a polymerizable liquid crystal compound, it is possible to improve the adhesion.
[0034] The tensile modulus of elasticity of the first adhesive layer 150 and the second adhesive layer 160 is measured by a method described later in the Examples. The optical laminate 100 may further include another adhesive layer between the first adhesive layer 150 and the second adhesive layer 160.
[0035] A curable adhesive containing a curable (polymerizable) compound is preferably used as the first adhesive forming the first adhesive layer 150 and the second adhesive forming the second adhesive layer 160. The curable adhesive is preferably an active energy ray curable adhesive that is cured by heating or irradiation with active energy rays such as ultraviolet light, visible light, electron beams, and X-rays. Examples of the curable adhesive include a radical polymerizable adhesive containing a radical polymerizable compound and a cationically polymerizable adhesive containing a cationically polymerizable compound.
[0036] The first adhesive is preferably a cationic polymerizable adhesive from the viewpoint of facilitating the formation of the first adhesive layer 150 having the above tensile modulus, and may contain a radical polymerizable compound together with the cationic polymerizable compound. The second adhesive is preferably a radical polymerizable adhesive from the viewpoint of facilitating the formation of the second adhesive layer 160 having the above tensile modulus, and may contain a cationic polymerizable compound together with the radical polymerizable compound. When the surface of the retarder 140 on which the second adhesive layer 160 is formed contains a cured product of a radical polymerizable compound, the second adhesive is a radical polymerizable adhesive, so that the adhesion between the retarder 140 and the polarizer 132 can be further improved. The tensile modulus of the first adhesive layer 150 and the second adhesive layer 160 can be adjusted by the type of adhesive, the degree of curing of the adhesive, and the like. In the first adhesive layer 150, the degree of curing of the first adhesive is preferably 98% or more, more preferably 99% or more. In the second adhesive layer 160, the degree of curing of the second adhesive is preferably 90% or more, more preferably 92% or more.
[0037] The thickness of the first adhesive layer 150 and the second adhesive layer 160 is preferably 20 μm or less, more preferably 15 μm or less, and even more preferably 10 μm or less, and may be 5 μm or less, or 0.05 μm or more, or may be 0.5 μm or more. When an active energy ray curable adhesive is used, the viscosity of the adhesive may be any viscosity that allows coating by various methods, and the viscosity at a temperature of 25° C. is preferably in the range of 10 to 1,000 mPa·sec, and more preferably in the range of 20 to 500 mPa·sec. If the viscosity is too low, it tends to be difficult to form a layer with a desired thickness. On the other hand, if the viscosity is too high, it tends to be difficult to flow, making it difficult to obtain a uniform coating film without unevenness. The viscosity here is a value measured at 10 rpm after adjusting the temperature of the adhesive to 25° C. using an E-type viscometer.
[0038] (cationic polymerizable adhesive) The cationic polymerizable compound contained in the cationic polymerizable adhesive refers to a compound or oligomer that undergoes cationic polymerization reaction and hardens when exposed to active energy rays such as ultraviolet light, visible light, electron beams, and X-rays or when heated, and examples of such compounds include epoxy compounds, oxetane compounds, and vinyl compounds. Among these, the preferred cationic polymerizable compound is an epoxy compound. An epoxy compound is a compound having one or more, preferably two or more, epoxy groups in the molecule. The epoxy compound may be used alone or in combination of two or more. Examples of the epoxy compound include alicyclic epoxy compounds, aromatic epoxy compounds, hydrogenated epoxy compounds, and aliphatic epoxy compounds. Among these, from the viewpoints of weather resistance, curing speed, and adhesiveness, the epoxy compound preferably contains an alicyclic epoxy compound or an aliphatic epoxy compound, and more preferably contains an alicyclic epoxy compound.
[0039] An alicyclic epoxy compound is a compound having one or more epoxy groups bonded to an alicyclic ring in the molecule. "Epoxy group bonded to an alicyclic ring" means a bridging oxygen atom -O- in the structure represented by the following formula (I). In the following formula (I), m is an integer of 2 to 5.
[0040] [ka]
[0041] (CH2) in the above formula (I) m Compounds in which one or more hydrogen atoms have been removed and the resulting group is bonded to another chemical structure can be called alicyclic epoxy compounds. (CH2) m One or more hydrogen atoms therein may be appropriately substituted with a straight-chain alkyl group such as a methyl group or an ethyl group.
[0042] Among them, alicyclic epoxy compounds having an epoxycyclopentane structure (where m=3 in the above formula (I)) or an epoxycyclohexane structure (where m=4 in the above formula (I)) have a high glass transition temperature of the cured product and are also advantageous in terms of adhesion between the polarizing film and the protective film. Specific examples of alicyclic epoxy compounds are listed below. Here, the compound names are listed first, followed by the corresponding chemical formulas, and the compound names and the corresponding chemical formulas are given the same symbols.
[0043] A: 3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate, B: 3,4-epoxy-6-methylcyclohexylmethyl 3,4-epoxy-6-methylcyclohexanecarboxylate, C: ethylene bis(3,4-epoxycyclohexane carboxylate), D: bis(3,4-epoxycyclohexylmethyl) adipate, E: bis(3,4-epoxy-6-methylcyclohexylmethyl) adipate, F: diethylene glycol bis(3,4-epoxycyclohexyl methyl ether), G: ethylene glycol bis(3,4-epoxycyclohexyl methyl ether), H: 2,3,14,15-diepoxy-7,11,18,21-tetraoxatrispiro[5.2.2.5.2.2]henicosane, I: 3-(3,4-epoxycyclohexyl)-8,9-epoxy-1,5-dioxaspiro[5.5]undecane, J: 4-vinylcyclohexene dioxide, K: Limonene dioxide, L: bis(2,3-epoxycyclopentyl) ether, M: Dicyclopentadiene dioxide.
[0044] [ka]
[0045] [ka]
[0046] The aromatic epoxy compound is a compound having an aromatic ring and an epoxy group in the molecule. Specific examples thereof include bisphenol type epoxy compounds or oligomers thereof, such as diglycidyl ether of bisphenol A, diglycidyl ether of bisphenol F, and diglycidyl ether of bisphenol S; novolac type epoxy resins, such as phenol novolac epoxy resin, cresol novolac epoxy resin, and hydroxybenzaldehyde phenol novolac epoxy resin; polyfunctional epoxy compounds, such as glycidyl ether of 2,2',4,4'-tetrahydroxydiphenylmethane and glycidyl ether of 2,2',4,4'-tetrahydroxybenzophenone; and polyfunctional epoxy resins, such as epoxidized polyvinylphenol.
[0047] The hydrogenated epoxy compound is a glycidyl ether of a polyol having an alicyclic ring, and can be a glycidyl ether of a nuclear hydrogenated polyhydroxy compound obtained by selectively hydrogenating an aromatic ring of an aromatic polyol under pressure in the presence of a catalyst. Specific examples of aromatic polyols include bisphenol type compounds such as bisphenol A, bisphenol F, and bisphenol S; novolac type resins such as phenol novolac resin, cresol novolac resin, and hydroxybenzaldehyde phenol novolac resin; and polyfunctional compounds such as tetrahydroxydiphenylmethane, tetrahydroxybenzophenone, and polyvinylphenol. The glycidyl ether can be obtained by reacting epichlorohydrin with an alicyclic polyol obtained by hydrogenating the aromatic ring of an aromatic polyol. Among the hydrogenated epoxy compounds, a preferred one is a hydrogenated diglycidyl ether of bisphenol A.
[0048] Aliphatic epoxy compounds are compounds having at least one oxirane ring (three-membered cyclic ether) bonded to an aliphatic carbon atom in the molecule. For example, monofunctional epoxy compounds such as butyl glycidyl ether and 2-ethylhexyl glycidyl ether; bifunctional epoxy compounds such as 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, and neopentyl glycol diglycidyl ether; trifunctional or higher epoxy compounds such as trimethylolpropane triglycidyl ether and pentaerythritol tetraglycidyl ether; and epoxy compounds having one epoxy group directly bonded to an alicyclic ring and an oxirane ring bonded to an aliphatic carbon atom, such as 4-vinylcyclohexene dioxide and limonene dioxide. Among them, from the viewpoint of adhesion between the polarizing film and the protective film, bifunctional epoxy compounds (also called aliphatic diepoxy compounds) having two oxirane rings bonded to an aliphatic carbon atom in the molecule are preferred. Such a suitable aliphatic diepoxy compound can be represented, for example, by the following formula (II).
[0049] [ka]
[0050] In the above formula (II), Y is an alkylene group having 2 to 9 carbon atoms, an alkylene group having a total of 4 to 9 carbon atoms and an ether bond therebetween, or a divalent hydrocarbon group having 6 to 18 carbon atoms and an alicyclic structure.
[0051] The aliphatic diepoxy compound represented by the above formula (II) is specifically a diglycidyl ether of an alkanediol, a diglycidyl ether of an oligoalkylene glycol having a repeating number of up to about 4, or a diglycidyl ether of an alicyclic diol.
[0052] Specific examples of diols (glycols) capable of forming the aliphatic diepoxy compound represented by the above formula (II) are given below. Alkanediols include ethylene glycol, propylene glycol, 1,3-propanediol, 2-methyl-1,3-propanediol, 2-butyl-2-ethyl-1,3-propanediol, 1,4-butanediol, neopentyl glycol, 3-methyl-2,4-pentanediol, 2,4-pentanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 2-methyl-2,4-pentanediol, 2,4-diethyl-1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 3,5-heptanediol, 1,8-octanediol, 2-methyl-1,8-octanediol, and 1,9-nonanediol. Examples of the oligoalkylene glycol include diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, etc. Examples of the alicyclic diol include cyclohexanediol, cyclohexanedimethanol, etc.
[0053] An oxetane compound, which is one of the cationic polymerizable compounds, is a compound containing one or more oxetane rings (oxetanyl groups) in the molecule, and specific examples thereof include 3-ethyl-3-hydroxymethyloxetane (also called oxetane alcohol), 2-ethylhexyloxetane, 1,4-bis[{(3-ethyloxetane-3-yl)methoxy}methyl]benzene (also called xylylene bisoxetane), 3-ethyl-3[{(3-ethyloxetane-3-yl)methoxy}methyl]oxetane, 3-ethyl-3-(phenoxymethyl)oxetane, and 3-(cyclohexyloxy)methyl-3-ethyloxetane. The oxetane compound may be used as the main component of the cationic polymerizable compound, or may be used in combination with an epoxy compound. By using an oxetane compound in combination, the curing speed and adhesiveness may be improved.
[0054] Examples of vinyl compounds that can be cationic polymerizable compounds include aliphatic or alicyclic vinyl ether compounds. Specific examples thereof include vinyl ethers of alkyl or alkenyl alcohols having 5 to 20 carbon atoms, such as n-amyl vinyl ether, i-amyl vinyl ether, n-hexyl vinyl ether, n-octyl vinyl ether, 2-ethylhexyl vinyl ether, n-dodecyl vinyl ether, stearyl vinyl ether, and oleyl vinyl ether; hydroxyl group-containing vinyl ethers, such as 2-hydroxyethyl vinyl ether, 3-hydroxypropyl vinyl ether, and 4-hydroxybutyl vinyl ether; vinyl ethers of monoalcohols having an aliphatic ring or an aromatic ring, such as cyclohexyl vinyl ether, 2-methylcyclohexyl vinyl ether, cyclohexylmethyl vinyl ether, and benzyl vinyl ether; glycerol monovinyl ether, 1,4-butanediol monovinyl ether, 1,4-butanediol monovinyl ether, and 1,4-butanediol monovinyl ether. Mono- to polyvinyl ethers of polyhydric alcohols such as hexanediol divinyl ether, 1,6-hexanediol divinyl ether, neopentyl glycol divinyl ether, pentaerythritol divinyl ether, pentaerythritol tetravinyl ether, trimethylolpropane divinyl ether, trimethylolpropane trivinyl ether, 1,4-dihydroxycyclohexane monovinyl ether, 1,4-dihydroxymethylcyclohexane monovinyl ether, and 1,4-dihydroxymethylcyclohexane divinyl ether; polyalkylene glycol mono- to divinyl ethers such as diethylene glycol divinyl ether, triethylene glycol divinyl ether, and diethylene glycol monobutyl monovinyl ether; and other vinyl ethers such as glycidyl vinyl ether and ethylene glycol vinyl ether methacrylate. The vinyl compound may be used as the main component of the cationic polymerizable compound, or may be used in combination with an epoxy compound, or an epoxy compound and an oxetane compound. By using a vinyl compound in combination, the curing speed and the viscosity of the adhesive may be improved.
[0055] The cationically polymerizable adhesive may further contain other curable compounds other than those mentioned above. Specific examples of the other curable compounds include other cationically polymerizable compounds other than those mentioned above, such as lactone compounds, cyclic acetal compounds, cyclic thioether compounds, and spiro orthoester compounds.
[0056] When the first adhesive is a cationic polymerizable adhesive, from the viewpoint of suppressing the outflow of dichroic dyes such as iodine from the polarizer 132, when the total amount of curable compounds contained in the first adhesive is taken as 100 mass%, the content of cationic polymerizable compounds (the content of all cationic polymerizable compounds contained in the first adhesive, or the total content when two or more types of cationic polymerizable compounds are contained) is preferably 80 weight % or more, more preferably 90 weight % or more, and even more preferably 100 weight %.
[0057] The first adhesive may be active energy ray curable or heat curable, but is preferably active energy ray curable. When the first adhesive is given active energy ray curability, it is preferable to blend a photocationic polymerization initiator into the adhesive. The photocationic polymerization initiator generates cationic species or Lewis acid by irradiation with active energy rays such as visible light, ultraviolet light, X-rays, or electron beams, and initiates a polymerization reaction of the cationic curable compound. The photocationic polymerization initiator acts catalytically with light, so that it has excellent storage stability and workability even when mixed with the photocationic curable compound. Examples of compounds that generate cationic species or Lewis acids by irradiation with active energy rays include onium salts such as aromatic iodonium salts and aromatic sulfonium salts, aromatic diazonium salts, and iron-arene complexes.
[0058] The aromatic iodonium salt is a compound having a diaryliodonium cation, and a typical example of the cation is a diphenyliodonium cation. The aromatic sulfonium salt is a compound having a triarylsulfonium cation, and a typical example of the cation is a triphenylsulfonium cation or a 4,4'-bis(diphenylsulfonio)diphenylsulfide cation. The aromatic diazonium salt is a compound having a diazonium cation, and a typical example of the cation is a benzenediazonium cation. The iron-arene complex is typically a cyclopentadienyliron(II) arene cation complex salt.
[0059] The cations shown above are paired with anions (negative ions) to form photocationic polymerization initiators. Examples of anions that form photocationic polymerization initiators include special phosphorus anions [(Rf) n PF 6-n ] - , Hexafluorophosphate anion PF6 - , Hexafluoro Antimonate anion SbF6 - , Pentafluorohydroxyantimonate anion SbF5(OH) - , hexafluoroarsenate anion AsF6 - , tetrafluoroborate anion BF4 - , tetrakis(pentafluorophenyl)borate anion B(C6F5)4 - Among them, from the viewpoint of the curability of the cationic polymerizable compound and the safety of the resulting adhesive layer, a special phosphorus anion [(Rf) n PF 6-n ] - , hexafluorophosphate aniline On PF6 - It is preferable that:
[0060] The photocationic polymerization initiator may be used alone or in combination of two or more. Among them, aromatic sulfonium salts are preferably used because they have ultraviolet absorbing properties even in the wavelength region around 300 nm, and therefore can provide a cured product with excellent curability, mechanical strength, and adhesive strength.
[0061] The amount of the photo-cationic polymerization initiator is usually 0.5 to 10 parts by weight, preferably 6 parts by weight or less, based on 100 parts by weight of the cationic polymerizable compound. By adding 0.5 parts by weight or more of the photo-cationic polymerization initiator, the cationic polymerizable compound can be sufficiently cured, and the obtained optical laminate can be given high mechanical strength and adhesive strength. On the other hand, if the amount is excessively large, the ionic substance in the cured product increases, so that the hygroscopicity of the cured product increases, and the durability of the polarizer may decrease. Examples of the photo-curable resin include (meth)acrylic resins, urethane resins, (meth)acrylic urethane resins, epoxy resins, and silicone resins. Examples of the water-soluble polymer include poly(meth)acrylamide-based polymers; polyvinyl alcohol, and vinyl alcohol-based polymers such as ethylene-vinyl alcohol copolymers, ethylene-vinyl acetate copolymers, and (meth)acrylic acid or its anhydride-vinyl alcohol copolymers; carboxyvinyl-based polymers; polyvinylpyrrolidone; starches; sodium alginate; and polyethylene oxide-based polymers.
[0062] (Radical polymerizable adhesive) The radical polymerizable compound contained in the radical polymerizable adhesive refers to a compound or oligomer that undergoes a radical polymerization reaction and hardens when exposed to active energy rays such as ultraviolet light, visible light, electron beams, and X-rays or when heated, and specifically includes a compound having an ethylenically unsaturated bond. Examples of the compound having an ethylenically unsaturated bond include (meth)acrylic compounds having one or more (meth)acryloyl groups in the molecule, as well as vinyl compounds such as styrene, styrene sulfonic acid, vinyl acetate, vinyl propionate, and N-vinyl-2-pyrrolidone. Among these, the preferred radical polymerizable compound is a (meth)acrylic compound.
[0063] Examples of the (meth)acrylic compound include (meth)acryloyl group-containing compounds such as (meth)acrylate monomers having at least one (meth)acryloyloxy group in the molecule, (meth)acrylamide monomers, and (meth)acryl oligomers having at least two (meth)acryloyl groups in the molecule, which are obtained by reacting two or more functional group-containing compounds. The (meth)acrylic oligomer is preferably a (meth)acrylate oligomer having at least two (meth)acryloyloxy groups in the molecule. The (meth)acrylic compound may be used alone or in combination of two or more.
[0064] Examples of the (meth)acrylate monomer include a monofunctional (meth)acrylate monomer having one (meth)acryloyloxy group in the molecule, a bifunctional (meth)acrylate monomer having two (meth)acryloyloxy groups in the molecule, and a polyfunctional (meth)acrylate monomer having three or more (meth)acryloyloxy groups in the molecule.
[0065] An example of a monofunctional (meth)acrylate monomer is an alkyl (meth)acrylate. In the alkyl (meth)acrylate, the alkyl group may be linear or branched as long as it has 3 or more carbon atoms. Specific examples of alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. In addition, aralkyl (meth)acrylates such as benzyl (meth)acrylate; (meth)acrylates of terpene alcohols such as isobornyl (meth)acrylate; (meth)acrylates having a tetrahydrofurfuryl structure such as tetrahydrofurfuryl (meth)acrylate; (meth)acrylates having a cycloalkyl group at the alkyl group moiety such as cyclohexyl (meth)acrylate, cyclohexylmethyl methacrylate, dicyclopentanyl acrylate, dicyclopentenyl (meth)acrylate, and 1,4-cyclohexanedimethanol monoacrylate; aminoalkyl (meth)acrylates such as N,N-dimethylaminoethyl (meth)acrylate; and (meth)acrylates having an ether bond at the alkyl group moiety such as 2-phenoxyethyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, ethyl carbitol (meth)acrylate, and phenoxypolyethylene glycol (meth)acrylate can also be used as monofunctional (meth)acrylate monomers.
[0066] Furthermore, monofunctional (meth)acrylates having a hydroxyl group at the alkyl moiety and monofunctional (meth)acrylates having a carboxyl group at the alkyl moiety can also be used. Specific examples of monofunctional (meth)acrylates having a hydroxyl group at the alkyl moiety include 2-hydroxyethyl (meth)acrylate, 2- or 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, trimethylolpropane mono(meth)acrylate, and pentaerythritol mono(meth)acrylate. Specific examples of monofunctional (meth)acrylates having a carboxyl group in the alkyl portion include 2-carboxyethyl (meth)acrylate, ω-carboxy-polycaprolactone (n≈2) mono(meth)acrylate, 1-[2-(meth)acryloyloxyethyl]phthalic acid, 1-[2-(meth)acryloyloxyethyl]hexahydrophthalic acid, 1-[2-(meth)acryloyloxyethyl]succinic acid, 4-[2-(meth)acryloyloxyethyl]trimellitic acid, and N-(meth)acryloyloxy-N',N'-dicarboxymethyl-p-phenylenediamine.
[0067] The (meth)acrylamide monomer is preferably a (meth)acrylamide having a substituent at the N-position, and a typical example of the substituent at the N-position is an alkyl group, but it may form a ring together with the nitrogen atom of the (meth)acrylamide, and this ring may have an oxygen atom as a ring member in addition to the carbon atom and the nitrogen atom of the (meth)acrylamide. Furthermore, a substituent such as an alkyl or oxo (=O) may be bonded to the carbon atom constituting the ring.
[0068] Specific examples of N-substituted (meth)acrylamides include N-alkyl (meth)acrylamides such as N-methyl (meth)acrylamide, N-ethyl (meth)acrylamide, N-isopropyl (meth)acrylamide, Nn-butyl (meth)acrylamide, Nt-butyl (meth)acrylamide, and N-hexyl (meth)acrylamide; and N,N-dialkyl (meth)acrylamides such as N,N-dimethyl (meth)acrylamide and N,N-diethyl (meth)acrylamide. The N-substituent may be an alkyl group having a hydroxyl group, and examples thereof include N-hydroxymethyl (meth)acrylamide, N-(2-hydroxyethyl) (meth)acrylamide, and N-(2-hydroxypropyl) (meth)acrylamide. Furthermore, specific examples of the N-substituted (meth)acrylamides forming the above-mentioned 5- or 6-membered ring include N-acryloylpyrrolidine, 3-acryloyl-2-oxazolidinone, 4-acryloylmorpholine, N-acryloylpiperidine, and N-methacryloylpiperidine.
[0069] Examples of the bifunctional (meth)acrylate monomer include alkylene glycol di(meth)acrylate, polyoxyalkylene glycol di(meth)acrylate, halogen-substituted alkylene glycol di(meth)acrylate, di(meth)acrylate of an aliphatic polyol, di(meth)acrylate of hydrogenated dicyclopentadiene or tricyclodecane dialkanol, di(meth)acrylate of dioxane glycol or dioxane dialkanol, di(meth)acrylate of an alkylene oxide adduct of bisphenol A or bisphenol F, and epoxy di(meth)acrylate of bisphenol A or bisphenol F.
[0070] More specific examples of the bifunctional (meth)acrylate monomer include ethylene glycol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, trimethylolpropane di(meth)acrylate, pentaerythritol di(meth)acrylate, ditrimethylolpropane di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, polytetramethylene glycol di(meth)acrylate, di(meth)acrylate, silicone di(meth)acrylate, di(meth)acrylate of hydroxypivalic acid neopentyl glycol ester, 2,2-bis[4-(meth)acryloyloxyethoxyethoxyphenyl]propane, 2,2-bis[4-(meth)acryloyloxyethoxyethoxycyclohexyl]propane, hydrogenated dicyclopentadienyl di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, 1,3-dioxane-2,5-diyl di(meth)acrylate [also known as dioxane glycol di(meth)acrylate], di(meth)acrylate of acetal compound of hydroxypivalaldehyde and trimethylolpropane [chemical name: 2-(2-hydroxy-1,1-dimethylethyl)-5-ethyl-5-hydroxymethyl-1,3-dioxane], tris(hydroxyethyl)isocyanurate di(meth)acrylate, etc.
[0071] Examples of the polyfunctional (meth)acrylate monomer having three or more functional groups include glycerin tri(meth)acrylate, alkoxylated glycerin tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta ... Representative examples include poly(meth)acrylates of trifunctional or higher aliphatic polyols such as taerythritol hexa(meth)acrylate, and other examples include poly(meth)acrylates of trifunctional or higher halogen-substituted polyols, tri(meth)acrylates of alkylene oxide adducts of glycerin, tri(meth)acrylates of alkylene oxide adducts of trimethylolpropane, 1,1,1-tris[(meth)acryloyloxyethoxyethoxy]propane, and tris(hydroxyethyl)isocyanurate tri(meth)acrylate.
[0072] On the other hand, the (meth)acrylic oligomer includes urethane (meth)acrylic oligomer, polyester (meth)acrylic oligomer, epoxy (meth)acrylic oligomer, and the like.
[0073] The urethane (meth)acrylic oligomer is a compound having a urethane bond (-NHCOO-) and at least two (meth)acryloyl groups in the molecule. Specifically, it may be a urethane reaction product between a hydroxyl group-containing (meth)acrylic monomer having at least one (meth)acryloyl group and at least one hydroxyl group in the molecule and a polyisocyanate, or a urethane reaction product between a terminal isocyanato group-containing urethane compound obtained by reacting a polyol with a polyisocyanate and a (meth)acrylic monomer having at least one (meth)acryloyl group and at least one hydroxyl group in the molecule.
[0074] The hydroxyl group-containing (meth)acrylic monomer used in the urethane reaction can be, for example, a hydroxyl group-containing (meth)acrylate monomer, specific examples of which include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, glycerin di(meth)acrylate, trimethylolpropane di(meth)acrylate, pentaerythritol tri(meth)acrylate, and dipentaerythritol penta(meth)acrylate. Specific examples of monomers other than the hydroxyl group-containing (meth)acrylate monomer include N-hydroxyalkyl (meth)acrylamide monomers such as N-hydroxyethyl (meth)acrylamide and N-methylol (meth)acrylamide.
[0075] Examples of polyisocyanates to be subjected to the urethanization reaction with the hydroxyl group-containing (meth)acrylic monomer include hexamethylene diisocyanate, lysine diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, tolylene diisocyanate, xylylene diisocyanate, diisocyanates obtained by hydrogenating aromatic isocyanates among these diisocyanates (e.g., hydrogenated tolylene diisocyanate, hydrogenated xylylene diisocyanate, etc.), di- or tri-isocyanates such as triphenylmethane triisocyanate and dibenzylbenzene triisocyanate, and polyisocyanates obtained by polymerizing the above diisocyanates.
[0076] In addition, examples of polyols that can be used to produce a urethane compound containing a terminal isocyanato group by reaction with a polyisocyanate include aromatic, aliphatic, and alicyclic polyols, as well as polyester polyols, polyether polyols, etc. Examples of aliphatic and alicyclic polyols include 1,4-butanediol, 1,6-hexanediol, ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, neopentyl glycol, trimethylolethane, trimethylolpropane, ditrimethylolpropane, pentaerythritol, dipentaerythritol, dimethylolheptane, dimethylolpropionic acid, dimethylolbutanoic acid, glycerin, and hydrogenated bisphenol A.
[0077] The polyester polyol is obtained by a dehydration condensation reaction between the above-mentioned polyol and a polybasic carboxylic acid or an anhydride thereof. Examples of the polybasic carboxylic acid or anhydride thereof, which are expressed by adding "(anhydride)" to the anhydride, include (anhydride) succinic acid, adipic acid, (anhydride) maleic acid, (anhydride) itaconic acid, (anhydride) trimellitic acid, (anhydride) pyromellitic acid, (anhydride) phthalic acid, (anhydride) isophthalic acid, terephthalic acid, and hexahydro(anhydride)phthalic acid.
[0078] The polyether polyol may be a polyalkylene glycol, or a polyoxyalkylene-modified polyol obtained by reacting the above-mentioned polyol or dihydroxybenzenes with an alkylene oxide.
[0079] The polyester (meth)acrylic oligomer is a compound having an ester bond and at least two (meth)acryloyl groups (typically (meth)acryloyloxy groups) in the molecule. Specifically, it can be obtained by a dehydration condensation reaction using (meth)acrylic acid, a polybasic carboxylic acid or its anhydride, and a polyol. Examples of the polybasic carboxylic acid or its anhydride used in the dehydration condensation reaction, which are expressed by adding "(anhydride)" to the anhydride that may be used, include (anhydride) succinic acid, adipic acid, (anhydride) maleic acid, (anhydride) itaconic acid, (anhydride) trimellitic acid, (anhydride) pyromellitic acid, hexahydrophthalic (anhydride), (anhydride) phthalic acid, isophthalic acid, terephthalic acid, etc. Examples of polyols used in the dehydration condensation reaction include 1,4-butanediol, 1,6-hexanediol, ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, neopentyl glycol, trimethylolethane, trimethylolpropane, ditrimethylolpropane, pentaerythritol, dipentaerythritol, dimethylolheptane, dimethylolpropionic acid, dimethylolbutanoic acid, glycerin, and hydrogenated bisphenol A.
[0080] The epoxy (meth)acrylic oligomer can be obtained, for example, by an addition reaction between a polyglycidyl ether and (meth)acrylic acid, and has at least two (meth)acryloyloxy groups in the molecule. Examples of the polyglycidyl ether used in the addition reaction include ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, and bisphenol A diglycidyl ether.
[0081] The polymerizable compound of the second adhesive may be composed only of a radically polymerizable compound, but may also further contain the above-mentioned cationic polymerizable compound.
[0082] The second adhesive may be active energy ray curable or heat curable, but is preferably active energy ray curable. When the second adhesive is given active energy ray curability, it is preferable to blend a photoradical polymerization initiator into the adhesive. The photoradical polymerization initiator initiates a polymerization reaction of a radical curable compound by irradiation with active energy rays such as visible light, ultraviolet light, X-rays, or electron beams. The photoradical polymerization initiator may be used alone or in combination of two or more kinds.
[0083] Specific examples of photoradical polymerization initiators include acetophenone-based initiators such as acetophenone, 3-methylacetophenone, benzyl dimethyl ketal, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropan-1-one, 2-methyl-1-[4-(methylthio)phenyl-2-morpholinopropan-1-one, and 2-hydroxy-2-methyl-1-phenylpropan-1-one; benzophenone-based initiators such as benzophenone, 4-chlorobenzophenone, and 4,4'-diaminobenzophenone; benzoin ether-based initiators such as benzoin propyl ether and benzoin ethyl ether; thioxanthone-based initiators such as 4-isopropylthioxanthone; and others, including xanthone, fluorenone, camphorquinone, benzaldehyde, and anthraquinone.
[0084] The amount of the photoradical polymerization initiator is usually 0.5 to 20 parts by weight, and preferably 1 to 6 parts by weight, based on 100 parts by weight of the radical polymerizable compound. By adding 0.5 parts by weight or more of the photoradical polymerization initiator, the radical polymerizable compound can be sufficiently cured.
[0085] (Additives) The first adhesive and / or the second adhesive may contain other additives as necessary. Specific examples of additives include ion trapping agents, antioxidants, chain transfer agents, polymerization accelerators (polyols, etc.), sensitizers, sensitization assistants, light stabilizers, tackifiers, thermoplastic resins, fillers, flow control agents, plasticizers, defoamers, leveling agents, silane coupling agents, dyes, antistatic agents, ultraviolet absorbers, and thermal polymerization initiators. Note that thermal polymerization initiators are used instead of photopolymerization initiators when preparing thermosetting adhesives. Examples of ion trapping agents include powdered inorganic compounds such as bismuth-, antimony-, magnesium-, aluminum-, calcium-, and titanium-based compounds, and mixtures thereof, and examples of antioxidants include hindered phenol-based antioxidants.
[0086] (Method of forming adhesive layer) The first adhesive layer 150 can be formed directly on the surface of the polarizer 132 opposite to the protective layer 131 side. The first adhesive layer 150 can be formed, for example, by applying the first adhesive to the surface of the polarizer 132 or the surface of the base film to be peeled off in a later step, or by dropping the first adhesive between the polarizer 132 and the base film, superposing the polarizer 132 (or the linear polarizing plate 130) and the base film via the uncured layer of the first adhesive, and laminating them by pressing from above and below using, for example, a laminating roll or the like, and then curing them by irradiating them with active energy rays (in the case of an active energy ray-curable adhesive) or by heating them (in the case of a thermosetting adhesive). The active energy rays may be irradiated from the polarizing plate 130 side or from the base film side.
[0087] The second adhesive layer 160 can be formed by applying a second adhesive to the surface of the first adhesive layer exposed by peeling off the base film used in the formation process of the first adhesive layer 150, or to the surface of the retarder 140, or by dropping the second adhesive between the first adhesive layer 150 and the retarder 140, stacking the linear polarizer 130 and the retarder 140 via the uncured layer of the second adhesive, pressing them from above and below using a lamination roll or the like to bond them together, and then irradiating them with active energy rays to cure them (in the case of an active energy ray-curable adhesive) or heating them to cure them (in the case of a thermosetting adhesive). The active energy rays may be irradiated from the linear polarizer 130 side or from the retarder 140 side.
[0088] The adhesive can be applied by various coating methods, such as a doctor blade, a wire bar, a die coater, a comma coater, a gravure coater, etc. Alternatively, a method of casting the adhesive between the layers to be bonded can be used.
[0089] Any suitable condition can be adopted as the irradiation condition of the active energy ray, so long as it can cure the active energy ray curable adhesive. For example, the acceleration voltage of the electron beam irradiation is preferably 5 kV to 300 kV, more preferably 10 kV to 250 kV. If the acceleration voltage is less than 5 kV, the electron beam may not reach the adhesive, resulting in insufficient curing, and if the acceleration voltage is more than 300 kV, the penetration force through the sample is too strong, causing the electron beam to bounce back and damaging the film or polarizer. The irradiation dose is 5 to 100 kGy, more preferably 10 to 75 kGy. If the irradiation dose is less than 5 kGy, the adhesive may not be cured sufficiently, and if it exceeds 100 kGy, the retardation layer may be damaged, causing a decrease in mechanical strength and yellowing, and the desired optical characteristics may not be obtained.
[0090] The electron beam irradiation is usually carried out in an inert gas atmosphere, but may be carried out in air or with a small amount of oxygen introduced, if necessary.
[0091] In the case of the ultraviolet ray curing type, the light irradiation intensity of the active energy ray curing adhesive is determined depending on the composition of the adhesive and is not particularly limited, but is preferably 10 to 1,000 mJ / cm. 2 It is preferable that the light irradiation intensity to the adhesive is 10 mJ / cm 2 If it is less than 1,000 mJ / cm, the reaction time will be too long and 2 If the light intensity exceeds this range, the heat radiated from the light source and the heat generated during polymerization of the adhesive may cause yellowing of the adhesive's constituent materials. The irradiation intensity is preferably an intensity in a wavelength range of 400 nm or less, and more preferably an intensity in a wavelength range of 280 to 320 nm. Irradiation is performed once or multiple times with such light irradiation intensity, and the integrated light amount is preferably 10 mJ / cm2. 2 More preferably, 100 to 1,000 mJ / cm 2 The integrated light intensity for the adhesive is set to 10 mJ / cm 2 If the cumulative light amount is less than 1,000 mJ / cm2, the generation of active species derived from the polymerization initiator is insufficient, and the adhesive is not cured sufficiently. 2 If the exposure time exceeds this limit, the exposure time will be extremely long, which is detrimental to improving productivity. In this case, the required cumulative light amount in the wavelength range (UVA (320-390 nm), UVB (280-320 nm), etc.) will differ depending on the type of film and the combination of adhesives used.
[0092] The light source used for polymerizing and curing the adhesive by irradiation with active energy rays in the present invention is not particularly limited, and examples thereof include low pressure mercury lamps, medium pressure mercury lamps, high pressure mercury lamps, ultra-high pressure mercury lamps, xenon lamps, halogen lamps, carbon arc lamps, tungsten lamps, gallium lamps, excimer lasers, LED light sources emitting light in the wavelength range of 380 to 440 nm, chemical lamps, black light lamps, microwave excited mercury lamps, and metal halide lamps. From the viewpoint of energy stability and device simplicity, ultraviolet light sources having an emission distribution at wavelengths of 420 nm or less are preferred.
[0093] Even when an active energy ray-curable adhesive is used, a heat treatment may be performed simultaneously with or after the irradiation of active energy rays. Before forming a coating layer of the adhesive, one or both of the bonding surfaces may be subjected to an easy-adhesion treatment such as a saponification treatment, a corona discharge treatment, a plasma treatment, a flame treatment, a primer treatment, or an anchor coating treatment.
[0094] [Phase difference body] The optical laminate 100 can function as a circular polarizing plate by including the linear polarizing plate 130 and the retardation body 140. Hereinafter, a configuration including the linear polarizing plate 130 and the retardation body 140 may also be referred to as a circular polarizing plate.
[0095] The retarder 140 preferably includes a first retardation layer 141 and a second retardation layer 142. The first retardation layer 141 and the second retardation layer 142 are preferably bonded together by an interlayer bonding layer 143 described later. The first retardation layer 141 and the second retardation layer 142 may have an overcoat layer for protecting the surface thereof, and a base film for supporting the first retardation layer 141 and the second retardation layer 142. Examples of the first retardation layer 141 and the second retardation layer 142 include a retardation layer (λ / 4 layer) that provides a retardation of λ / 4, a retardation layer (λ / 2 layer) that provides a retardation of λ / 2, and a positive C layer.
[0096] The retarder 140 preferably includes a λ / 4 layer, and more preferably includes at least one of a λ / 4 layer and a λ / 2 layer or a positive C layer.
[0097] In the retarder 140, a first retardation layer 141 and a second retardation layer 142 are laminated in this order from the polarizer 132 side. When the retarder includes a λ / 2 layer, the first retardation layer 141 is a λ / 2 layer, and the second retardation layer 142 is a λ / 4 layer. When the retarder 140 includes a positive C layer, the first retardation layer 141 is a positive C layer and the second retardation layer 142 is a λ / 4 layer, or the first retardation layer 141 is a λ / 4 layer and the second retardation layer 142 is a positive C layer. The thickness of the retarder 140 is, for example, 0.1 μm to 50 μm, preferably 0.5 μm to 30 μm, and more preferably 1 μm to 10 μm.
[0098] The retarder 140 preferably contains a cured product of a polymerizable liquid crystal compound. In such a configuration, although it may be difficult to obtain adhesion to the polarizer 132, according to the present invention, high adhesion can be obtained. The first retarder layer 141 of the retarder 140 preferably contains a cured product of a polymerizable liquid crystal compound. In such a configuration, although it may be difficult to obtain adhesion to the polarizer 132, according to the present invention, high adhesion can be obtained. The surface of the first retarder layer 141 facing the polarizer 132 may contain a polymerizable liquid crystal compound, or may contain a cured product of a radical polymerizable liquid crystal compound as the polymerizable liquid crystal compound. In such a configuration, although it may be difficult to obtain adhesion to the polarizer 132, according to the present invention, high adhesion can be obtained. The surface of the first retarder layer 141 facing the polarizer 132 may be the surface of a layer that exhibits retardation, or may be an alignment film.
[0099] The second retardation layer 142 may be formed from a resin film exemplified as the material of the resin film described above, or may be formed from a layer in which a polymerizable liquid crystal compound is hardened. The first retardation layer 141 and the second retardation layer 142 may further include an alignment film and a base film. The first retardation layer 141 having an alignment film and the second retardation layer 142 having an alignment film may be treated as one unit member.
[0100] When the first retardation layer 141 and the second retardation layer 142 are formed from a layer formed by curing a polymerizable liquid crystal compound, they can be formed by applying a composition containing a polymerizable liquid crystal compound to a substrate film and curing it. An alignment film may be formed between the substrate film and the coating layer. The alignment film may be formed from a composition containing a polymerizable liquid crystal compound. The material and thickness of the substrate film may be the same as the material and thickness of the resin film. When the first retardation layer 141 and the second retardation layer 142 are formed from a layer formed by curing a polymerizable liquid crystal compound, they may be incorporated into the laminate in a form having an alignment film and a substrate film.
[0101] The alignment film has an alignment regulating force that aligns the liquid crystal compound contained in the liquid crystal layer that exhibits retardation formed on the alignment film in a desired direction. Examples of the alignment film include an alignment polymer film made of an alignment polymer, a photoalignment polymer film made of a photoalignment polymer, and a groove alignment film having a concave-convex pattern or a plurality of grooves on the film surface. The thickness of the alignment film is usually 0.01 to 10 μm, and preferably 0.01 to 5 μm.
[0102] The oriented polymer film can be formed by applying a composition in which an oriented polymer is dissolved in a solvent to a substrate film, removing the solvent, and optionally performing a rubbing treatment. In this case, the orientation control force of the oriented polymer layer formed from the oriented polymer can be arbitrarily adjusted by the surface state of the oriented polymer and the rubbing conditions.
[0103] The photo-alignable polymer film can be formed by applying a composition containing a polymer or monomer having a photoreactive group and a solvent to a substrate film and irradiating the composition with polarized light. In this case, the alignment control force of the photo-alignable polymer film can be arbitrarily adjusted by the conditions of irradiating the photo-alignable polymer with polarized light, etc.
[0104] The groove alignment film can be formed, for example, by a method of forming an uneven pattern on the surface of a photosensitive polyimide film by exposing the surface of the film through an exposure mask having slits in a pattern shape, developing the film, etc.; a method of forming an uncured film of active energy ray curable resin on a plate-shaped master having grooves on its surface, transferring this film to a substrate film and curing the film; a method of forming an uncured layer of active energy ray curable resin on a substrate film, and pressing a roll-shaped master having unevenness against this layer to form unevenness and then curing the layer.
[0105] The liquid crystal layer exhibiting retardation imparts a predetermined retardation to light, and examples thereof include a layer exhibiting retardation in the form of a λ / 2 layer and a layer exhibiting retardation in the form of a λ / 4 layer.
[0106] The liquid crystal layer exhibiting retardation can be formed using a known liquid crystal compound. The type of liquid crystal compound is not particularly limited, and a rod-shaped liquid crystal compound, a discotic liquid crystal compound, or a mixture thereof can be used. The liquid crystal compound may be a polymer liquid crystal compound, a polymerizable liquid crystal compound, or a mixture thereof. Examples of the liquid crystal compound include those described in JP-T-11-513019, JP-A-2005-289980, JP-A-2007-108732, JP-A-2010-244038, JP-A-2010-31223, JP-A-2010-270108, JP-A-2011-6360, JP-A-2011-207765, JP-A-2016-81035, WO 2017 / 043438, and JP-T-2011-207765.
[0107] For example, when a polymerizable liquid crystal compound is used, a composition containing the polymerizable liquid crystal compound is applied onto an alignment film to form a coating film, and the coating film is cured to form a liquid crystal layer exhibiting retardation. The thickness of the retardation layer is preferably 0.5 μm to 10 μm, and more preferably 0.5 to 5 μm. The composition containing a polymerizable liquid crystal compound may contain, in addition to the liquid crystal compound, a polymerization initiator, a polymerizable monomer, a surfactant, a solvent, an adhesion improver, a plasticizer, an alignment agent, etc. Examples of a method for applying the composition containing a polymerizable liquid crystal compound include known methods such as a die coating method. Examples of a method for curing the composition containing a polymerizable liquid crystal compound include known methods such as irradiation with active energy rays (e.g., ultraviolet rays).
[0108] A polarizing plate in which the polarizer 132 and the retarder 140 are arranged so that the absorption axis of the polarizer 132 and the slow axis of the retarder 140 form a predetermined angle has an anti-reflection function, that is, can function as a circular polarizing plate. When the retarder 140 includes a λ / 4 layer, the angle between the absorption axis of the polarizer 132 and the slow axis of the λ / 4 layer can be 45°±10°. The first retardation layer 141 and the second retardation layer 142 may have a normal wavelength dispersion property or a reverse wavelength dispersion property. The λ / 4 layer preferably has a reverse wavelength dispersion property.
[0109] [Interlayer lamination layer] The interlayer bonding layer 143 is disposed between the first retardation layer 141 and the second retardation layer 142, and has a function of bonding the first retardation layer 141 and the second retardation layer 142. The interlayer bonding layer 143 can be made of an adhesive or a pressure-sensitive adhesive. The interlayer bonding layer 143 is preferably an adhesive layer.
[0110] The thickness of the interlayer bonding layer 143 is not particularly limited, but when a pressure sensitive adhesive layer is used as the interlayer bonding layer 143, it is preferably 1 μm or more, and may be 5 μm or more, and is usually 50 μm or less, and may be 25 μm or less. When an adhesive layer is used as the interlayer bonding layer 143, the thickness of the interlayer bonding layer 143 is preferably 0.1 μm or more, and may be 0.5 μm or more, and is preferably 10 μm or less, and may be 5 μm or less.
[0111] The adhesive may be formed by combining one or more of water-based adhesives, active energy ray curing adhesives, etc. Examples of water-based adhesives include polyvinyl alcohol-based resin aqueous solutions and water-based two-liquid urethane-based emulsion adhesives. The active energy ray curing adhesive is an adhesive that is cured by irradiation with active energy rays such as ultraviolet rays, and examples of the adhesive include an adhesive containing a polymerizable compound and a photopolymerization initiator, an adhesive containing a photoreactive resin, and an adhesive containing a binder resin and a photoreactive crosslinking agent. Examples of the polymerizable compound include photopolymerizable monomers such as photocurable epoxy monomers, photocurable acrylic monomers, and photocurable urethane monomers, and oligomers derived from these monomers. Examples of the photopolymerization initiator include a compound containing a substance that generates active species such as neutral radicals, anion radicals, and cation radicals when irradiated with active energy rays such as ultraviolet rays.
[0112] The adhesive can be composed of an adhesive composition having a base polymer such as a (meth)acrylic, rubber, urethane, ester, silicone, or polyvinyl ether resin. Among them, an adhesive composition having a base polymer of a (meth)acrylic resin, which is excellent in transparency, weather resistance, heat resistance, etc., is preferable. The adhesive composition may be of an active energy ray curing type or a heat curing type.
[0113] As the (meth)acrylic resin (base polymer) used in the pressure-sensitive adhesive composition, for example, a polymer or copolymer containing one or more (meth)acrylic acid esters as monomers, such as butyl (meth)acrylate, ethyl (meth)acrylate, isooctyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate, is preferably used. It is preferable to copolymerize a polar monomer into the base polymer. Examples of the polar monomer include monomers having a carboxyl group, a hydroxyl group, an amide group, an amino group, an epoxy group, and the like, such as (meth)acrylic acid, 2-hydroxypropyl (meth)acrylate, hydroxyethyl (meth)acrylate, (meth)acrylamide, N,N-dimethylaminoethyl (meth)acrylate, and glycidyl (meth)acrylate.
[0114] The adhesive composition can contain a crosslinking agent together with the base polymer. Examples of the crosslinking agent include divalent or higher metal ions that form a carboxylate metal salt with a carboxyl group; polyamine compounds that form an amide bond with a carboxyl group; polyepoxy compounds or polyols that form an ester bond with a carboxyl group; and polyisocyanate compounds that form an amide bond with a carboxyl group. Among these, polyisocyanate compounds are preferred.
[0115] The active energy ray curable adhesive composition is an adhesive composition that has a property of being cured by irradiation with active energy rays such as ultraviolet rays or electron beams, has adhesiveness even before irradiation with active energy rays, can be adhered to an adherend such as a film, and can be cured by irradiation with active energy rays to adjust the adhesive strength. The active energy ray curable adhesive composition is preferably an ultraviolet ray curable type. The active energy ray curable adhesive composition further contains an active energy ray polymerizable compound in addition to a base polymer and a crosslinking agent. If necessary, a photopolymerization initiator, a photosensitizer, etc. may also be contained.
[0116] The pressure-sensitive adhesive composition may contain additives such as a light diffusing agent, a resin other than the base polymer, a tackifier, a filler (metal powder or other inorganic powder, etc.), an antioxidant, an ultraviolet absorber, a dye, a pigment, a colorant, an antifoaming agent, a corrosion inhibitor, and a photopolymerization initiator.
[0117] <Method of manufacturing optical laminate> The method for producing the optical laminate is not particularly limited. One embodiment includes a step of applying a first adhesive to a surface of a polarizer and curing the first adhesive to form a first adhesive layer, and a step of laminating the first adhesive layer formed on the surface of the polarizer and the retardation body with a second adhesive interposed therebetween and curing the second adhesive to form a second adhesive layer.
[0118] <Image display device> The image display device includes an image display panel and the optical laminate. In the image display device, the optical laminate can be arranged, for example, on the front surface of the image display panel. The image display panel is not particularly limited, and examples thereof include a liquid crystal display panel, an organic electroluminescence (organic EL) display panel, an inorganic electroluminescence (inorganic EL) display panel, a plasma display panel, and a field emission display panel. The image display device can be configured by arranging the optical laminate functioning as a circular polarizer on the viewing side of the organic EL display device.
[0119] The image display device according to the present invention can be used as mobile devices such as smartphones and tablets, televisions, digital photo frames, electronic signs, measuring instruments and gauges, office equipment, medical equipment, computing equipment, etc. The image display device according to the present invention has excellent durability even when used in harsh environments. EXAMPLES
[0120] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples. In the following examples, the following were used as the radical polymerizable compound, photoradical polymerization initiator, cationic polymerizable compound, photocationic polymerization initiator, and additives that constitute the adhesive.
[0121] (Radical polymerizable compound) [1] Radical polymerizable compound 1: 1,4-cyclohexanedimethanol monoacrylate (trade name "CHDMMA" obtained from Nippon Kasei Co., Ltd.) [2] Radical polymerizable compound 2: 4-hydroxybutyl acrylate (trade name "4HBA" obtained from Nippon Kasei Co., Ltd.) [3] Radical polymerizable compound 3: Bifunctional urethane acrylate (product name "UV-3700B" obtained from Mitsubishi Chemical Corporation)
[0122] (Photoradical polymerization initiator) [4] Photoradical polymerization initiator 1: 1-hydroxycyclohexyl phenyl ketone (trade name "Omnirad184" obtained from BASF) [5] Photoradical polymerization initiator 2: 2,4,6-trimethylbenzoyldiphenylphosphine oxide (trade name "TPO" obtained from BASF)
[0123] (cationically polymerizable compound) [6] Cationic polymerizable compound 1: 3',4'-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate (trade name "CEL2021P" obtained from Daicel Corporation) [7] Cationic polymerizable compound 2: 1,2-epoxy-4-(2-oxiranyl)cyclohexane adduct of 2,2-bis(hydroxymethyl)-1-butanol (trade name "EHPE3150" available from Daicel Corporation) [8] Cationic polymerizable compound 3: 3-ethyl-3-{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane (trade name "OXT-221" obtained from Toagosei Co., Ltd.)
[0124] (Photocationic polymerization initiator) [9] Photocationic polymerization initiator 1: Triarylsulfonium salt (product name "CPI-100P" obtained from San-Apro Co., Ltd., 50% by weight propylene carbonate solution)
[0125] (Additives)
[10] Photosensitizer 1: 1,4-diethoxynaphthalene (trade name "Anthracure ET2201" obtained from Kawasaki Kasei Chemical Industries, Ltd.)
[11] Photosensitizer 2: 9,10-dibutoxyanthracene (trade name "Anthracure UVS-1331" obtained from Kawasaki Kasei Chemical Industries, Ltd.)
[0126] <Production Example 1: Preparation of radically polymerizable adhesive> The following radical polymerizable compound and photoradical polymerization initiator were weighed out in the following mixing ratio into a 20 mL screw tube, mixed and degassed to prepare a liquid radical polymerizable adhesive that cures when irradiated with ultraviolet light. Hereinafter, this adhesive is also referred to as "Adhesive R."
[0127] 25 parts by mass of radical polymerizable compound 1, 65 parts by mass of radical polymerizable compound 2, 10 parts by mass of radical polymerizable compound 3, Photoradical polymerization initiator 1: 3 parts by mass, Photoradical polymerization initiator 2: 1 part by mass.
[0128] <Production Example 2: Preparation of cationic polymerizable adhesive> The cationic polymerizable compound, photocationic polymerization initiator, and additives described below were weighed out in the mixing ratio described below into a 20 mL screw tube, mixed, and degassed to prepare a liquid cationic polymerizable adhesive that cures when irradiated with ultraviolet light. Hereinafter, this adhesive is also referred to as "adhesive C1."
[0129] Cationic polymerizable compound 1 32.5 parts by mass, Cationic polymerizable compound 2 7.5 parts by mass, Cationic polymerizable compound 3 60.0 parts by mass, Photocationic polymerization initiator 1: 2.25 parts by mass (solid content equivalent), Photosensitizer 1 2 parts by weight.
[0130] <Production Example 3: Preparation of cationic polymerizable adhesive> The cationic polymerizable compound, photocationic polymerization initiator, and additives described below were weighed out in the mixing ratio described below into a 20 mL screw tube, mixed, and degassed to prepare a liquid cationic polymerizable adhesive that hardens when irradiated with ultraviolet light. Hereinafter, this adhesive is also referred to as "adhesive C2."
[0131] Cationic polymerizable compound 1 32.5 parts by mass, Cationic polymerizable compound 2 7.5 parts by mass, Cationic polymerizable compound 3 60.0 parts by mass, Photocationic polymerization initiator 1: 2.25 parts by mass (solid content equivalent), Photosensitizer 1, 1 part by weight Photosensitizer 2 2 parts by weight.
[0132] <Preparation of adhesive layer> We prepared a commercially available adhesive layer 1 with a separate film (a layer made of an acrylic adhesive and having a thickness of 15 μm) and an adhesive layer 2 with a separate film (a layer made of an acrylic adhesive and having a thickness of 5 μm).
[0133] <Example 1: Preparation of optical laminate> The linear polarizing plate was produced by laminating and bonding a multilayer film to a polyvinyl alcohol (PVA) resin film (polarizer, thickness 8 μm) obtained by iodine dyeing and stretching. A cycloolefin polymer (COP) film (thickness 24 μm) with a hard coat layer (HC) protected by a polyethylene terephthalate (PET) protective film was bonded to the polarizer with water glue and dried to obtain a polarizer (polarizing plate) with a protective layer. The exposed surface of the polarizer was subjected to a corona treatment, and a biaxially stretched COP film (thickness 52 μm) was bonded to that surface via an ultraviolet-curing adhesive (adhesive C1), and ultraviolet (UV) light was applied at 200 mJ / cm. 2The biaxially stretched COP film side was irradiated with UVA output of 200 mJ / cm. After aging at room temperature overnight, the biaxially stretched COP film was peeled off. This resulted in a linear polarizing plate having a first adhesive layer, which is a cured layer of adhesive C1, on the surface of the polarizer. Separately, a retardation body (an integrated product in which a reverse dispersion λ / 4 retardation layer / positive C layer / protective film (PET) are laminated) was prepared, and the linear polarizing plate and the retardation body were bonded together using adhesive R. Specifically, corona treatment was performed on the exposed surface of the first adhesive layer and the exposed surface of the reverse dispersion λ / 4 retardation layer, and the two were laminated together via an ultraviolet-curable adhesive (adhesive R), and UV light was irradiated at 200 mJ / cm. 2 The retarder was irradiated with UVA intensity of 1000 nm from the retarder side to bond the linear polarizer and the retarder. As a result, an optical laminate was obtained in which the second adhesive layer, which is a cured layer of the adhesive R, was interposed between the reverse dispersion λ / 4 retardation layer and the first adhesive layer (cured layer of the adhesive C1) so as to be in contact with both. Thereafter, the protective film (PET) of the retarder in the optical laminate was peeled off, and the exposed surface of the positive C layer was subjected to corona treatment, and then the pressure-sensitive adhesive layer 1 with the separate film was attached. In this manner, the optical laminate of Example 1 was obtained. The optical laminate of Example 1 has a configuration in which the cured layer of the adhesive C1 (first adhesive layer) and the cured layer of the adhesive R (second adhesive layer) are interposed between the polarizer and the reverse dispersion λ / 4 retardation layer.
[0134] <Comparative Example 1: Preparation of optical laminate> An optical laminate of Comparative Example 1 was produced in the same manner as in Example 1, except that the first adhesive layer was not formed and adhesive C2 was used instead of adhesive R to bond the linear polarizer and the retardation film. Specifically, the cured layer of adhesive C2 was formed by subjecting the exposed surfaces of the polarizer and the reverse dispersion λ / 4 retardation film to corona treatment, laminating the two together via adhesive C2, and then irradiating them with UV light at 200 mJ / cm. 2 The retardation film was irradiated with UVA light at a UVA intensity of 1000 nm from the side of the retardation film to bond the linear polarizing plate and the retardation film together. The optical laminate of Comparative Example 1 has a structure in which a cured layer of the adhesive C2 is interposed between the polarizer and the reverse dispersion λ / 4 retardation film.
[0135] <Comparative Example 2: Preparation of optical laminate> An optical laminate of Comparative Example 2 was produced in the same manner as in Example 1, except that the first adhesive layer was not formed and the pressure-sensitive adhesive layer 2 was used instead of the adhesive R to bond the linear polarizer and the retardation film. Specifically, the bonding using the pressure-sensitive adhesive layer 2 was performed by subjecting the exposed surfaces of the polarizer and the reverse dispersion λ / 4 retardation layer to a corona treatment, and laminating both of them via the pressure-sensitive adhesive layer 2. The optical laminate of Comparative Example 2 has a configuration in which the pressure-sensitive adhesive layer 2 is interposed between the polarizer and the reverse dispersion λ / 4 retardation layer.
[0136] <Measurement of tensile modulus> Adhesive C1, Adhesive C2, and Adhesive R were each applied to a biaxially stretched COP film (thickness 52 μm), and UV light was applied at 200 mJ / cm 2 The adhesive layer was irradiated with a UVA intensity of 1000 nm to form an adhesive layer having an average thickness of 0.3 μm after curing. Each adhesive layer and the pressure-sensitive adhesive layer 2 having a thickness of 5 μm were uniaxially stretched at a speed of 1 mm / min in an environment at a temperature of 25° C. using an autograph (manufactured by Shimadzu Corporation, product name: AG-IS), and the tensile modulus was calculated from the value of the obtained stress-strain curve. Table 1 shows the tensile modulus of each layer at a temperature of 25° C.
[0137] [Table 1]
[0138] <Durability test (high temperature and humidity conditions, high temperature conditions)> Each optical laminate of Example 1, Comparative Example 1, and Comparative Example 2 was cut to a size of 30 mm x 30 mm, the separate film attached to the adhesive layer 1 was peeled off, and the laminate was attached to Corning alkali-free glass (product name: Eagle XG, 40 mm x 40 mm x thickness 0.7 mm), and autoclaved at a temperature of 50 ° C. to prepare a sample. Each sample was left in an oven set to high temperature and high humidity conditions (temperature 80 ° C., relative humidity 90% RH) for 24 hours. The polarization degree (Py1) at a wavelength of 550 nm before being put into the oven and the polarization degree (Py2) at a wavelength of 550 nm after being left in the oven for 24 hours were measured with a spectrophotometer (V-7100 manufactured by JASCO), and the change amount ΔPy was calculated based on the following formula. ΔPy = Py2 - Py1
[0139] In addition, the reflected hue (a1*, b1*) before placing in the oven and the reflected hue (a2*, b2*) after leaving in the oven for 24 hours were measured with a portable spectrophotometer (Konica Minolta, product name: CM-2600d) by placing the sample on a metal reflector, and the amount of change, Δc*, was calculated based on the following formula. Δc*=√{(a2*-a1*) 2 +(b2*-b1*) 2}
[0140] Each sample was left in an oven set under high temperature conditions (temperature 105° C., relative humidity 0% RH) for 30 minutes, and Δc* was calculated in the same manner as in the case of high temperature and high humidity conditions described above.
[0141] Table 2 shows the calculated ΔPy and Δc* values.
[0142] <Adhesion test> Each optical laminate of Example 1, Comparative Example 1, and Comparative Example 2 was cut into a size of 30 mm x 30 mm, the separate film attached to the adhesive layer 1 was peeled off, and the laminate was attached to Corning's alkali-free glass (product name: Eagle XG, 40 mm x 40 mm x thickness 0.7 mm), and autoclaved at a temperature of 50 ° C. to prepare a sample. After peeling off the HC-attached COP film on the outermost surface of each sample, a cross was cut with a cutter knife at intervals of 1 mm in an area of 10 mm x 10 mm to prepare 10 x 10 (100) squares. Nichiban Cellotape (registered trademark) was attached so as to be in contact with all the squares, firmly adhered, and peeled off at an angle of 45 degrees diagonally upward in one go. The number of remaining squares remaining on the glass side by this operation was measured. Table 2 shows the number of remaining squares.
[0143] [Table 2] [Explanation of symbols]
[0144] 100 optical laminate, 130 linear polarizing plate, 131 protective layer, 132 polarizer, 140 retardation body, 141 first retardation layer, 142 second retardation layer, 143 interlayer lamination layer.
Claims
1. An optical laminate comprising a polarizer containing a polyvinyl alcohol-based resin and a retardation film containing a cured product of a polymerizable liquid crystal compound, a first adhesive layer provided between the polarizer and the retardation film and in contact with the polarizer, and a second adhesive layer provided in contact with the retardation film, The optical laminate, wherein the second adhesive layer has a tensile modulus of elasticity of 1900 MPa or less at a temperature of 25°C.
2. The optical laminate according to claim 1 , wherein the first adhesive layer has a tensile modulus of elasticity of 2000 MPa or more at a temperature of 25° C.
3. the first adhesive layer is a cured layer of a cationic polymerizable adhesive, The optical laminate according to claim 1 , wherein the second adhesive layer is a layer of a cured product of a radically polymerizable adhesive.
4. The optical laminate according to any one of claims 1 to 3, wherein the retardation layer includes a λ / 4 layer.
5. The optical laminate according to any one of claims 1 to 4, which is an anti-reflection polarizing plate.
6. An image display device comprising: an image display panel; and the optical laminate according to claim 5 arranged in front of the image display panel.
7. The image display device according to claim 6 , wherein the image display panel is an organic electroluminescence (EL) display panel.
8. A method for producing an optical laminate according to any one of claims 1 to 5, applying a first adhesive to a surface of the polarizer and curing the first adhesive to form a first adhesive layer; laminating the first adhesive layer formed on the surface of the polarizer and the retardation film with a second adhesive therebetween, and curing the second adhesive to form a second adhesive layer.
Citation Information
Patent Citations
Adhesive sheet
JP1997033723A
Manufacturing method of polarizer, polarizer, polarizing plate, optical film, and image display device
JP2013105036A
Polarizing plate
JP2016126070A
Optical film with adhesive and image display device
JP2016151580A
Optical laminate
JP2018141962A